Neuter gender in the languages of Aru - Schapper, Antoinette (Wacana, Journal of the Humanities of Indonesia, 2015)
This paper examines gender agreement in three little-known languages of the Aru Islands and places them within the larger pattern of "neuter gender" in eastern Indonesia. For each language, I look first at the variety of agreement targets that are controlled by gendered nouns. Secondly, I look at the semantics of nouns that control agreement. I show that whilst having a strongly semantic base involving animacy, gender in Aru languages is a grammatical category in which many nouns denoting certain types of entities that lack discernable biological animacy are assigned to the same gender as that of animate referents. I conclude by considering the system of gender in proto-Aru.